Oscillating towards herself. The poetic pendulum in “I am the bad girl in history” - Lobato Hoyos, Joan Susann (2021)
This present study analyzes the levels of representation and figuration of the poem “I am the bad girl in the history” in order to discover the role played by the poetic self from the perspective of Paul Valéry’s poetic pendulum. Thus, through an eclectic analysis, in which it considers proposals from rhetoric to cognitive semantics, we will achieve a deeper understanding of dialectics, based on the concepts of presence and absence anchored in a symmetry of meaning and sound, which underlies in the emblematic poem by María Emilia Cornejo.